From rookeries to foraging grounds: understanding regional connectivity and genetic diversity in hawksbill turtles - Christine A. Madden Hof; Amelia A. Desbiens; Jeff Kinch; Nancy N. Fitzsimmons; Hayley Versace; Angelique Amon; Nathan McIntyre; Kathy A. Townsend; Michael P. Jensen (Frontiers in Marine Science, 2023)
This study investigated the genetic structure, diversity, and migratory patterns of hawksbill turtles ( Eretmochelys imbricata ) from two nesting locations in Papua New Guinea (PNG) using mitochondrial DNA (mtDNA) sequencing and satellite telemetry. Tissue samples collected from nesting female hawksbill turtles (n=75) in PNG revealed a total of 6 haplotypes from the Conflict Group site and 5 haplotypes from Kavieng site, with the Conflict Group and Kavieng samples significantly differing from one another and all other known Asia-Pacific stocks. This finding expands our understanding of the genetic stock structure of hawksbill turtles in the Asia-Pacific region, resulting in 9 Management Units (MUs) now published. Satellite tracking of 15 hawksbill turtles revealed that all individuals migrated from the Conflict Group westerly towards foraging areas in eastern Australia (93%) and PNG (7%). With a mean migration path distance of 1241 ± 108 km, three distinct migration strategies were used by the 10 hawksbill turtles that made it to their foraging grounds in the I) eastern Torres Strait, II) Far North Queensland, and III) western PNG waters. A broad scope of home-range strategies and sizes (95% UD) were used, and in comparison to other studies further postulates that hawksbills are connected to non-specific foraging grounds associated with food source availability. This study provides for the first time in PNG essential insights into hawksbill turtle population structure and connectivity in the western Pacific region, highlighting the importance of effectively conserving and managing this critically endangered species as distinct population stocks. Furthermore, we make recommendations for national and regional conservation strategies and transboundary management to ensure the long-term survival and recovery of western Pacific’s hawksbill turtle populations.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Intra-annual density fluctuations in silver fir are triggered by drought conditions - S. Versace; G. Battipaglia; R. Tognetti; V. Garfì; D. Gianelle; P. Cherubini (Trees, 2021)

A comprehensive framework for empirical modeling of landslides induced by rainfall: the Generalized FLaIR Model (GFM) - D. L. De Luca; P. Versace (Landslides, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Aspects of the biology of Galaxias maculatus - L. J. B. Laurenson; R. P. French; P. Jones; D. Ierodiaconou; S. Gray; V. L. Versace; A. Rattray; S. Brown; J. Monk (Journal of Fish Biology, 2012)
The biology of three landlocked and a riverine population of Galaxias maculatus were examined in western Victoria, Australia. All systems supported reproducing populations of these fish, including Lake Corangamite which had salinities that on occasion reached 82. Spawning sites in Lake Corangamite were located in adjacent tributaries and not in the main lake as was the case for other populations. The smallest fish were found in the fresh water Lake Purrumbete and the largest in the hypersaline Lake Corangamite. The size at which 50% of the population attained sexual maturity varied across sites, with fish maturing at a smaller size in Lake Purrumbete, followed by the Merri River, Lake Bullen Merri and Lake Corangamite. Condition was higher in the freshwater Lake Purrumbete and there was no relationship between condition and temperature, conductivity, turbidity and pH; but there was a positive relationship between condition and dissolved oxygen. Length frequency analysis suggested that the majority of fishes live for a year.

Population Genetic Structuring in Acanthopagrus butcheri (Pisces: Sparidae): Does Low Gene Flow Among Estuaries Apply to Both Sexes? - Christopher P. Burridge; Vincent L. Versace (Marine Biotechnology, 2007)